If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3x + 12 = 0 Reorder the terms: 12 + 9x + 3x = 0 Combine like terms: 9x + 3x = 12x 12 + 12x = 0 Solving 12 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 0 + -12 12x = 0 + -12 Combine like terms: 0 + -12 = -12 12x = -12 Divide each side by '12'. x = -1 Simplifying x = -1
| solve-5(2x-11)=(2x-3)-11 | | 300-16t^2=0 | | 3n-2+2(2n+1)=6n+7 | | 6+5x=2.666 | | 264=8(-5a-7) | | 9+9=180 | | -8(6b+6)=-96 | | 3(x+10)-2(-x+10)=10 | | 27/16-8/9= | | -6c+q=-9c+7 | | 81=-3(5-8b) | | 45+2.50=9.25 | | 6.5x+7=1.5x+32 | | -4+6x=-.375 | | 5(x+8)+3(-x+8)=-2 | | 1/30x=1/40x | | -357=-7(-7x+2) | | -7n-4(6-4n)=-39+4n | | 20=500-60m | | -5(8m-4)=260 | | 8+.4x=4.4 | | 100=2(2+6k) | | 2+5y-y=y-2+25 | | 86=2(8m-5) | | 3(x+14)+4(x+7)=-35 | | 8-4v=-5(v+4)+5v | | 206=x+7x | | 206=x+(x+7) | | -18+2x=8(6x-8) | | 60=10x+10 | | 3x+2(3x+1)=11 | | 49/70=x/100 |